1992
DOI: 10.2134/jeq1992.00472425002100020004x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Some Metals by Legumes and Their Extractability from Acid Mine Spoils

Abstract: A greenhouse study was conducted to investigate the growth (dry matter yield) of selected legume cover crops; phytoaccumulation of metals such as Zn, Mn, Pb, Cu, Ni, and Al, and extractability of heavy metals from three different Alabama acid mine spoils. The spoils were amended based on soil test recommended levels of N, P, K, Ca, and Mg prior to plant growth. Metals were extracted by three extractants (Mehlich 1, DTPA, and 0.1 M HCI) and values correlated with their accumulation by the selected legumes. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Numerous studies have investigated the phytoavailability of As and Pb from various sources including the availability of As or Pb to crops grown on soils amended with sewage sludge (Lutrick et al, 1982;Narwal et al, 1983;Keefer et al, 1986), slag (Bunzl et al, 2001), phosphorus fertilizers (Goodroad and Caldwell, 1979), or fungicidal sprays (Merry et al, 1983;Merry et al, 1986); and As and Pb uptake by crops from the soils contaminated by mining and smelting activities (Xian, 1989;Davies, 1992;Levy et al, 1992;Taylor et al, 1992;Pichtel and Salt, 1998;Klassen et al, 2000;Roussel et al, 2000). The added As or Pb reacts with Fe and other soil constituents (Goldberg, 1986;Ainsworth et al, 1994;Manning and Goldberg, 1996;Sauvé et al, 2000;Saha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the phytoavailability of As and Pb from various sources including the availability of As or Pb to crops grown on soils amended with sewage sludge (Lutrick et al, 1982;Narwal et al, 1983;Keefer et al, 1986), slag (Bunzl et al, 2001), phosphorus fertilizers (Goodroad and Caldwell, 1979), or fungicidal sprays (Merry et al, 1983;Merry et al, 1986); and As and Pb uptake by crops from the soils contaminated by mining and smelting activities (Xian, 1989;Davies, 1992;Levy et al, 1992;Taylor et al, 1992;Pichtel and Salt, 1998;Klassen et al, 2000;Roussel et al, 2000). The added As or Pb reacts with Fe and other soil constituents (Goldberg, 1986;Ainsworth et al, 1994;Manning and Goldberg, 1996;Sauvé et al, 2000;Saha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the effects of surface mining and the mobilization of heavy metals (Bhuiyan et al 2010;Rashed 2010;Ciszewski et al 2012), and have often revealed a high degree of metal toxicity in mine spoils and soils affected by the oxidation of pyritic material (Pérez and de Anta 1992;Taylor et al 1992Taylor et al , 1993Monterroso et al 1999;Clark et al 2001;Iavazzo et al 2012). However, information on the occurrence of AMLs all over the world together with the pollution database is not available in the form of a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
“…Métodos, como extrações químicas, simples ou seqüenciais, permitem inferir sobre a disponibilidade dos metais em substratos e conhecer a dinâmica de equilíbrio químico entre as formas dos metais (Amaral Sobrinho et al, 1997). Assim, soluções vêm sendo testadas para extrair os metais pesados do solo, incluindo água, agentes extratores ácidos, quelantes e redutores (Taylor et al, 1992;Pierzynski & Schwab, 1993;Abreu et al, 1995).…”
Section: Seção IX -Poluição Do Solo E Qualidade Ambiental Introduçãounclassified